Pengaruh Inkubasi dan Non Inkubasi Pada Pemeriksaan Kadar Hemoglobin dengan Menggunakan Metode Sahli Di Puskesmas Sedau Kecematan Narmada Kabupaten Lombok Barat - Mas’uniwati Mas’uniwati; Ahmad Azwan; Baiq Naili Dewi Atika; Dwi Kartika Risfianty; Pahmi Husain (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2022)
Nutritional problems in Indonesia and in developing countries in general are still dominated by the problem site, namely the problem of lack of protein energy (KEP), Iron Anemia, problems due to iodine deficiency (IDD), vitamin A deficiency problems (KVA). Iron anemia is the most common in the community, the occurrence of Iron Anemia can be caused by several factors including iron content in daily food, very low absorption of iron from food, the presence of parasites in the body, and loss of blood due to accidents or accidents. surgery due to illness. Therefore, the researchers tried to examine the effect of Incubation and Non-Incubation on the examination of Hemoglobin levels using the Sahli Method using the Experimental Method which is Cross Sectional. This study aims to determine whether there is an effect of incubation and non-incubation on the results of examination of hemoglobin levels using the Sahli method at Sedau Public Health Center, Narmada District, West Lombok, NTB.